Determinants of economic growth in Hong Kong: The role of stock market development - Sin-yu Ho (Cogent Economics & Finance, 2018)
We assessed the impact of stock market development on growth in Hong Kong for the period 1986Q2 to 2015Q4. By constructing a composite index of stock market development and controlling for the key determinants of growth, we found stock market development to promote growth both in the short and long run. We further constructed an alternative index of stock market development and found this conclusion to be robust. Our findings are broadly consistent with the growth experience of Hong Kong. Policies meant to promote stock market development may enhance growth in Hong Kong as well.
Keywords: 330; determinants; economic growth; stock market development; Hong Kong